Functional Attributes of Synovial Fluid from Osteoarthritic Knee Exacerbate Cellular Inflammation and Metabolic Stress, and Fosters Monocyte to Macrophage Differentiation - Vanshika Srivastava; Abhay Harsulkar; Shama Aphale; Aare Märtson; Sulev Kõks; Priya Kulkarni; Shantanu Deshpande (Biomedicines)
Background: Besides conventional norms that recognize synovial fluid (SF) as a joint lubricant, nutritional channel, and a diagnostic tool in knee osteoarthritis (kOA), based on the authors previous studies, this study aims to define functional role of SF in kOA. Methods: U937, a monocytic, human myeloid cell line, was induced with progressive grades of kOA SF, and the induction response was assessed on various pro-inflammatory parameters. This ‘SF challenge test model’ was further extended to determine the impact of SF on U937 differentiation using macrophage-specific markers and associated transcription factor genes. Mitochondrial membrane potential changes in SF-treated cells were evaluated with fluorescent JC-1 probe. Results: a significant increase in nitric oxide, matrix metalloproteinase (MMP) 1, 13, and vascular endothelial growth factor (VEGF)-1 was noted in the induced cells. A marked increase was seen in CD68, CD86, and the transcription factors –activator protein (AP)-1, interferon regulatory factor (IRF)-1, and signal transducer and activator of transcription (STAT)-6 in the SF-treated cells indicating active monocytes to macrophage differentiation. Reduced mitochondrial membrane potential was reflected by a reduced red-to-green ratio in JC-1 staining. Conclusions: these results underline the active role of OA SF in stimulating and maintaining inflammation in joint cells, fostering monocyte differentiation into pro-inflammatory macrophages. The decline in the membrane potential suggestive of additional inflammatory pathway in OA via the release of pro-apoptotic factors and damaged associated molecular patterns (DAMPs) within the cells. Overall, biochemical modulation of SF warrants a potential approach to intervene inflammatory cascade in OA and mitigate its progression.